Pengembangan Sistem Penilaian Matematika Berbasis Kompetensi di Sekolah Menengah Pertama Kabupaten Lombok Tengah - Husnul Laili (ISLAMIKA, 2019)
This study aims to produce a competence-based Mathematics assessment system that can be applied to reveal the competence of Year VII students of Junior High Schools (JHSs) in semester II in Central Lombok Regency. The study shows the following findings. First, the assessment guideline consists of components in the form of: (1) a syllabus, (2) an assessment system design, (3) criteria for SKBM/KKM, (4) criteria for the score proportion, (5) a matrix of the continuous assessment process, (6) an indicator analysis, (7) a format of the analysis of each aspect, (8) a format of the analysis of students’ learning mastery, (9) a format of the learning achievement report, and (10) a format of the score attainment graph. Second, the assessment instrument consists of the items dealing with (1) identifying set elements and subsets presented in the Venn diagram and solving items related to daily problems using the concept of a set, (2) determining the relation of two lines and determining the measures of the angles, (3) determining the properties of the angles when two lines intersect or two parallel lines are intersected by another line, (4) determining perimeters of a triangle and a quadrilateral and solving items related to daily problems using the concepts of a triangle and a quadrilateral. The research instrument validity is obtained through the theoretical analysis of test items by experts in Mathematics and the instrument satisfies the validity criteria. The reliability coefficient obtained is 0.883.